Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate - Panahandeh, Yousef; Pourjam, Ebrahim; Abolafia, Joaquín; Roshan-Bakhsh, Ali; Mojerlou, Shideh; Afshar, Farahnaz Jahanshahi; Pedram, Majid (Zootaxa, 2019)
Labrys khuzestanensis n. sp. was recovered from the rhizosphere of a palm tree in southwestern Iran and described using morphological and molecular data. The new species was characterized by combination of the following features: its 590–675 μm long body, finely annulated cuticle in light microscopy (LM), lateral field with two smooth incisures, cephalic region dorso-ventrally flattened with protuberant, elongate and laterally extended labial plate, appearing a V-shaped piece in lateral view, amphidial openings as longitudinal slits confined to labial plate in scanning electron microscopic (SEM) images, stylet 7.5–9.0 μm long, elongated fusiform median bulb with faint valvular apparatus, excretory pore wide with moderately sclerotized duct and elongate filiform tail with finely rounded tip. Compared to four currently known species under the genus, the new species has a remarkably larger and more prominent labial plate as revealed by SEM and trapezoid cephalic region under LM. The molecular phylogenetic analyses of the new species using partial SSU rDNA revealed it has close affinity with three species of Labrys (L. chinensis, L. fuzhouensis and L. filiformis) in Bayesian inference (BI) and maximum likelihood (ML) methods and occupied a placement inside their clade. L. fujianensis, the other species of the genus, occupied a distant placement to the aforementioned clade. This is the second species of Labrys being originally described from Iran, representing the third species of Labrys occurring in the country.